Finite element method based analysis of lower body structural strength on rekarya ev electric car - Wibisono, Kristian; Aryadi, Widya (Universitas Negeri Semarang, 2024)
In line with current technological developments, the use of electric vehicles is expected to increase due to their environmentally friendly nature—primarily because they produce no exhaust emissions. One of the critical structural components of an electric car is the lower body. The lower body of the Rekarya EV has been specifically designed to accommodate three rows of seating. This study aims to evaluate the structural strength of the Rekarya EV's lower body under static loading conditions by analyzing von Mises stress, displacement, and safety factor values. The analysis was carried out using the Finite Element Method (FEM) through Autodesk Inventor Professional 2020. A static stress analysis was performed using ASTM A36 steel material with three different thickness variations: 1.0 mm, 1.2 mm, and 1.4 mm. The resulting von Mises stress values were 72.88 MPa, 62.24 MPa, and 51.66 MPa, respectively. The corresponding displacement values were 1.366 mm, 1.295 mm, and 1.212 mm. The calculated safety factors were 3.41, 3.99, and 4.8. Additionally, the total weight of the lower body for each thickness was calculated as 88.012 kg, 100.823 kg, and 113.613 kg. The results indicate that all three thickness variations provide adequate safety factors; however, increasing material thickness significantly affects the overall weight of the structure. Therefore, a balance between strength and weight must be considered in the design process.